2022
DOI: 10.1186/s12955-022-02040-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-related quality of life in patients with heart failure: a cross-sectional study in Saudi Arabia

Abstract: Background As a precarious clinical condition and a public health problem, heart failure (HF) is associated with a significant burden of morbidity, mortality, and health care costs. As almost all of the published research has been conducted in Western countries, there is a need for culturally relevant studies in Saudi Arabia. This is the first study to investigate health-related quality of life (HRQoL) and its associated factors among Saudi patients with HF in the Qassim region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
4
12
0
Order By: Relevance
“…Alharbi et al in Saudi Arabia [ 16 ] and Rodríguez-Artalejo et al in Spain [ 17 ] also noted that the RP domain had the lowest scores, consistent with our study. Heart failure is characterized by a cluster of symptoms and signs resulting from structural or functional cardiac abnormalities [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Alharbi et al in Saudi Arabia [ 16 ] and Rodríguez-Artalejo et al in Spain [ 17 ] also noted that the RP domain had the lowest scores, consistent with our study. Heart failure is characterized by a cluster of symptoms and signs resulting from structural or functional cardiac abnormalities [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Upon conducting subgroup analysis based on variables such as age, gender, or LVEF, no statistically significant differences were observed in PCS, MCS, and overall HRQoL scores. [16] and Rodríguez-Artalejo et al in Spain [17] also noted that the RP domain had the lowest scores, consistent with our study. Heart failure is characterized by a cluster of symptoms and signs resulting from structural or functional cardiac abnormalities [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[5] This phenomenon can be attributed to the increasing prevalence of obesity and significant socioeconomic transformations that have resulted in the uptake of detrimental behaviors, including the consumption of high-calorie foods, tobacco use, and insufficient physical activity. [17] A systematic review of real-world observational studies of Sac/Val in patients with HFrEF also reported variations in the baseline characteristics between the studies compared with PARADIGM-HF. [18] Similar to our study, patients included in the systematic review had a higher incidence of DM and more patients were on MRA than in the PARADIGM-HF study.…”
Section: Discussionmentioning
confidence: 99%
“…This is important considering that lower health-related quality of life predicts mortality and re-hospitalization in HF regardless of symptoms severity and LV dysfunction [ 10 ]. This was reflected among Saudi HF patients among whom impaired quality of life was reported [ 11 ] and involvement in a structured management program for HF improved quality of life, reduced mortality as well as hospitalization [ 12 , 13 ]).…”
Section: Introductionmentioning
confidence: 99%